2014
DOI: 10.1155/2014/461393
|View full text |Cite
|
Sign up to set email alerts
|

The Study of Naphthoquinones and Their Complexes with DNA by Using Raman Spectroscopy and Surface Enhanced Raman Spectroscopy: New Insight into Interactions of DNA with Plant Secondary Metabolites

Abstract: Naphthoquinones represent the group of plant secondary metabolites with cytotoxic properties based on their ability to generate reactive oxygen species and interfere with the processes of cell respiration. Due to this fact, the possible cytotoxic mechanisms on cellular and subcellular levels are investigated intensively. There are many targets of cytotoxic action on the cellular level; however, DNA is a critical target of many cytotoxic compounds. Due to the cytotoxic properties of naphthoquinones, it is neces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 88 publications
1
14
0
Order By: Relevance
“…It should be noted that, PLSR over the high concentration range, up to 50 μM, (Figure A) results in a spectral profile which is similar to those of DOX and ACT (Figure ) exhibiting strong features at 785 cm −1 (DNA backbone O─P─O) and 813 cm −1 (RNA O─P─O phosphodiester band stretching), while regression over the lower concentration up to the IC 50 of 1.2 ± 0.2 μM showed a decrease in features at 728, 830 and 1425 cm −1 , related to DNA B form and an increase in features at 668 and 675 cm −1 , related to DNA A form, indicative of conformational changes due to partial transition of the DNA B form to DNA A form due to Cisp binding .…”
Section: Raman Microspectroscopy For Chemotherapeutic Pre‐clinical Scmentioning
confidence: 58%
“…It should be noted that, PLSR over the high concentration range, up to 50 μM, (Figure A) results in a spectral profile which is similar to those of DOX and ACT (Figure ) exhibiting strong features at 785 cm −1 (DNA backbone O─P─O) and 813 cm −1 (RNA O─P─O phosphodiester band stretching), while regression over the lower concentration up to the IC 50 of 1.2 ± 0.2 μM showed a decrease in features at 728, 830 and 1425 cm −1 , related to DNA B form and an increase in features at 668 and 675 cm −1 , related to DNA A form, indicative of conformational changes due to partial transition of the DNA B form to DNA A form due to Cisp binding .…”
Section: Raman Microspectroscopy For Chemotherapeutic Pre‐clinical Scmentioning
confidence: 58%
“…In addition, it was also found that juglone, lawsone and 1,4-naphthoquinone induced reactive oxygen species [38,41] and the subsequent programmed cell death [17]. Naphthoquinones are able to inhibit some enzymes and proteins and bind to DNA, thereby modifying its conformation [23,42,43].…”
Section: Discussionmentioning
confidence: 99%
“…This fact suggests that lawsone inhibits auxin-induced growth indirectly by producing reactive oxygen species (ROS) that then increase cytosol Ca 2+ , which is followed by an inhibition of the PM H + -ATPase activity [60,61,62,63,64]. It was also found that lawsone has the ability to bind to DNA, which leads to a nonspecific interaction and the transition of Β-DNA into an A-DNA conformation [43].…”
Section: Discussionmentioning
confidence: 99%
“…And, we used SERS to further research the mode of interaction between gigantol and the AR gene. Experimental studies in recent years showed that SERS allows the Raman scattering signal of the tested material enhancement 1014-1015 times, and 10 -7 M of DNA can also be detected (Yang M et al, 2016;Kim S et al, 2016;Li Y et al, 2016;Vaverkova et al, 2014). In this experiment, the SERS peaks of AR gene were greatly enhanced with the increasing amounts gigantol.…”
Section: Discussionmentioning
confidence: 54%